Neuromuscular adaptations to plyometric exercises in late-phase ACL reconstruction rehabilitation: A case report - Fadhilah, Siti; Pristianto, Arif; Mardianto, Halim (Svāsthya: Trends in General Medicine and Public Health, 2025)
Postanterior cruciate ligament (ACL) reconstruction rehabilitation poses significant challenges in restoring optimal neuromuscular function and athletic performance.This study aimed to evaluate the therapeutic efficacy of a structured plyometric exercise protocol on muscle strength, dynamic balance, and functional outcomes in young athletes who underwent ACL reconstruction. A single-case study of a 16-year-old male soccer athlete who underwent right anterior cruciate ligament (ACL) reconstruction was conducted. The intervention comprised three sessions of progressive plyometric exercises over a seven-day period. Outcomes were assessed via a modified sphygmomanometer test for muscle strength, the Y balance test for dynamic balance, and the Tegner Lysholm knee scoring scale for functional ability. Knee flexor strength improved from 50 to 100 mmHg (100% increase), and extensor strength increased from 110 to 130 mmHg (18.2% increase). The dynamic balance composite score increased from 88% to 108%. The functional performance on the Tegner-Lysholm scale improved from 90 to 95 points, primarily because of reduced pain scores. This case demonstrates that a structured plyometric exercise protocol may effectively improve muscle strength, dynamic balance, and functional performance during late-stage ACL rehabilitation. These findings suggest the potential utility of return-to-sport protocols, although large-scale investigations are warranted.